EVALUATION OF ANTIOXIDANT ACTIVITY OF EXTRACT COMBINATION OF GINGER AND LEMONGRASS - Faradiba; Syarif, Rezki Amriati; Anggrayni, Anggi; Praditha, Elyana; Amalia, Alifiya Reski (Universal Journal of Pharmaceutical Research, 2025)
Aim and objective: This study to determine the antioxidant activity of the combination of ginger (Zingiber officinale) and lemongrass (Cymbopogon citratus) on reducing DPPH (2,2-diphenyl-1-picrylhydrazyl). Methods: Quantitative measurement of the antioxidant activity of ginger and lemongrass extracts, as well as a combination of both with a concentration ratio of 1:1, 2:1, 1:2 using a UV-Vis spectrophotometer at a wavelength of 516 nm to determine the IC50 value. Results: IC50 value of ginger extract 10.76 µg/mL, lemongrass extract 26.69 µg/mL, IC50 value 6.69 µg/mL for combination with concentration ratio 1:1, IC50 value 3.32 µg/mL for combination with concentration ratio 2:1. IC50 value 9.34 µg/mL for combination with concentration ratio 1:2 Conclusions: The combination of ginger and lemongrass extracts has synergistic antioxidant activity that can increase the antioxidant effect from the strong category to very strong category. Peer Review History: Received 17 October 2024; Reviewed 9 November; Accepted 18 December; Available online 15 January 2025 Academic Editor: Dr. Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewers: Antonio José de Jesus Evangelista, Federal University of Ceará, UFC, Brazil, tony_biomed@hotmail.com Dr. Sangeetha Arullappan, Universiti Tunku Abdul Rahman, Malaysia, sangeetha@utar.edu.my